PENGARUH PERSEPSI KOMPETENSI DASAR DOSEN TERHADAP MOTIVASI BELAJAR MAHASISWA - Reni Febriani; Sudaryono Sudaryono; Siti Rohmah (FKIP, Universitas Banten Jaya, 2019)
This study aims determine the effect of Lecturer on the Motivation of Student Learning Result of Accounting Education Program Education Faculty at Banten Jaya University. This research uses quantitative approach method. The subjects of the study are students of Accounting Education Program Education Faculty at Banten Jaya University. In this research data technique used is questionnaire or questionnaire to 69 respondentsfrom 82 Accounting Education study program students.The method used in this research is descriptive research method, and practical analysis of data analysis, validity test, reliability test, normality test, homogeneity test, analysis, simple linear regression analysis, significance test (f test, t test, coefficient of determination).From the results of data analysis that has been done to obtain the results that include the category